Silver and the Dutch Revolt: The Obsession with Spanish Silver in the Seventeenth-Century Dutch Atlantic - Klooster, Wim (The sixteenth century journal, 2020)
The article discusses the relations between the Netherlands and Spain during the Dutch War of Independence and throughout the seventeenth century, focusing on Dutch efforts to garner hard currency in the form of Spanish silver from their colonies. It discusses the Netherlands burgeoning international trade during the period, smuggling, the West India Company and its attacks on Spanish Atlantic trade vessels, and the Dutch East India Company.